2023
DOI: 10.1590/1413-81232023284.14132022en
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sleep quality in university students

Abstract: To investigate factors associated with poor sleep quality. A cross-sectional study was conducted in 2019 with random sampling. Information on sleep was obtained using the Mini Sleep Questionnaire (MSQ). Independent variables included sociodemographic, behavioural, academic and psychological health characteristics. Adjusted analyzes were performed using Poisson regression. A total of 996 undergraduate students participated in the study. The poor sleep quality affected 23.1% of the sample (95%CI 20.5-25.9), rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…A study revealed that family income or wealth can serve as supportive resources for promoting healthy sleep among university students (23), and evidence from cross-sectional studies suggests that students from lower socioeconomic backgrounds are more likely to report sleep disturbances and poor sleep quality (24). Additionally, a study found that poor socioeconomic status increases the risk of developing sleep disorders (25). Risky behaviors such as lack of physical activity (26), smoking (27) and regular alcohol consumption (17) are common among university students and contribute to poor sleep quality in this population.…”
Section: Introductionmentioning
confidence: 99%
“…A study revealed that family income or wealth can serve as supportive resources for promoting healthy sleep among university students (23), and evidence from cross-sectional studies suggests that students from lower socioeconomic backgrounds are more likely to report sleep disturbances and poor sleep quality (24). Additionally, a study found that poor socioeconomic status increases the risk of developing sleep disorders (25). Risky behaviors such as lack of physical activity (26), smoking (27) and regular alcohol consumption (17) are common among university students and contribute to poor sleep quality in this population.…”
Section: Introductionmentioning
confidence: 99%